Green Human Resource Management as an Educational Framework for Environmental Performance: Evidence from the Public Sector - Aryati, Ana Sofia; Fasieh, Muhammad Fajrul Islam (Jurnal Pendidikan Progresif, 2025)
Green Human Resource Management as an Educational Framework for Environmental Performance: Evidence from the Public Sector. Objective: This study aims to investigate the impact of Green Human Resource Management (GHRM) practices on environmental performance (GP) within government organizations. It seeks to fill the existing research gap by examining the mediating roles of green organizational commitment (GOC) and employee green behavior (EGB) in the relationship between GHRM and GP. Methods: The research employed a quantitative approach using a structured survey distributed to employees across various government organizations. Data were analyzed using Structural Equation Modeling (SEM) to assess the direct and indirect effects of GHRM on EP, with GOC and EGB as mediating variables. Findings: The study found that GHRM has a statistically significant positive effect on EP. Specifically, GHRM practices increased GP by p-value (p < 0.008). Furthermore, both GOC and EGB partially mediated this relationship. Among the two mediators, GOC demonstrated a stronger mediating effect, with a p-value of 0.000 for the total influence, compared to EGB, which had a p-value of 0.016. These results emphasize that fostering organizational commitment plays a more pivotal role in enhancing the effectiveness of GHRM strategies. Conclusion: The findings underscore the critical role of GHRM in promoting superior environmental performance, both directly and through fostering organizational commitment and individual green behaviors. The stronger mediating role of GOC suggests that cultivating a shared sense of environmental responsibility within the organization is key to maximizing the impact of green HR practices. Practical Implications: These findings provide actionable insights for policymakers and organizational leaders. For instance, local governments and corporate HR departments should prioritize investing in GHRM-specific training programs to strengthen employees' green commitment and behaviors. Additionally, embedding environmental values into organizational culture and HR frameworks can significantly enhance sustainable outcomes. Firms that institutionalize GHRM as part of their strategic operations are more likely to achieve long-term environmental compliance and resilience. Keywords: green human resource management; green organizational commitment; environmental performance, employee green behavior, green training.